2013
DOI: 10.1016/j.jphysparis.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

“Disorganized in time”: Impact of bottom-up and top-down negative emotion generation on memory formation among healthy and traumatized adolescents

Abstract: "Travelling in time," a central feature of episodic memory is severely affected among individuals with Post Traumatic Stress Disorder (PTSD) with two opposite effects: vivid traumatic memories are unorganized in temporality (bottom-up processes), non-traumatic personal memories tend to lack spatio-temporal details and false recognitions occur more frequently that in the general population (top-down processes). To test the effect of these two types of processes (i.e. bottom-up and top-down) on emotional memory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 55 publications
0
34
0
Order By: Relevance
“…Among studies involving tasks with picture stimuli: five studies used a recognition memory task (Chemtob et al, 1999; Whalley et al, 2009; Brohawn et al, 2010; Mickley Steinmetz et al, 2012; Patel et al, 2016); one study used a recognition memory task after an oddball task (Guillery-Girard et al, 2013); one study used an item-method directed forgetting task (Baumann et al, 2013); and another study used a delayed memory free recall test (Nicholson et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among studies involving tasks with picture stimuli: five studies used a recognition memory task (Chemtob et al, 1999; Whalley et al, 2009; Brohawn et al, 2010; Mickley Steinmetz et al, 2012; Patel et al, 2016); one study used a recognition memory task after an oddball task (Guillery-Girard et al, 2013); one study used an item-method directed forgetting task (Baumann et al, 2013); and another study used a delayed memory free recall test (Nicholson et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies included only women, three studies included only men, and nine studies included both. Sixteen studies included only adult PTSD patients, and two studies included only adolescent and/or child PTSD patients (Moradi et al, 2000; Guillery-Girard et al, 2013). Eleven studies involved patients with one or two specific types of traumatic event (Zeitlin and McNally, 1991; Vrana et al, 1995; McNally et al, 1998; Chemtob et al, 1999; Moradi et al, 2000; Bremner et al, 2003; Golier et al, 2003; Zoellner et al, 2003; Baumann et al, 2013; Thomaes et al, 2013; Herzog et al, 2017), six studies involved patients with different traumatic events (Whalley et al, 2009; Brohawn et al, 2010; Mickley Steinmetz et al, 2012; Tapia et al, 2012; Nicholson et al, 2014; Patel et al, 2016), and one study did not specify (Guillery-Girard et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We, and others, have previously shown that the hippocampus presents both structural and functional abnormalities in adult (Bremner et al, 2003) and adolescent abuse-related PTSD (Dégeilh et al, 2017; Postel et al, 2019). Symptoms in adolescent PTSD largely reflect those present in adults, with deficits in attentional control (Guillery-Girard et al, 2013), autobiographical memory (Crane et al, 2014; Ogle et al, 2013) and fear extinction (Keding and Herringa, 2015). What happens at the brain level?…”
Section: Introductionmentioning
confidence: 99%
“…In particular, failure to inhibit fear learning and fear memory consolidation are considered to be precipitating factors in the development of PTSD [ 14 ]. With regards to cognition, PTSD patients showed significantly less activation in sensory association areas, suggesting diversion of attention from the presented stimuli, perhaps due to increased focus on the elicited trauma memory [ 15 - 17 ]. It has been suggested that cognitive impairments exhibited by people with PTSD result from intrusive flashback memories that transiently interfere with ongoing cognitive processing [ 17 ].…”
Section: Introductionmentioning
confidence: 99%